Pengaruh Kondisi Keuangan dan Motivasi Pada Minat Calon Sarjana Akuntansi Universitas Tidar Dalam Mengikuti Pendidikan Profesi Akuntansi Di Masa Pandemi Covid-19 - Riza Aziza Sumarna; Ari Nurul Fatimah (Institut Bisnis dan Informatika Kesatuan, 2021)
The purpose of this study was to find out whether financial conditions and motivation affect the interest of accounting students at Tidar Magelang University in participating in the Accounting Profession Education (PPAk) during the Covid-19 pandemic. The method of collecting data is through a questionnaire with a sample of 50 respondents. Meanwhile, the data analysis model used is Multiple Linear Regression. The results of this study indicate that the financial condition variable does not have a significant effect and the motivation variable has a significant influence on the interest of accounting students to take the Accounting Profession Education (PPAk) during the Covid-19 pandemic.